Bulgaria - Efficiency Analysis of STI Programs - World Bank (Washington, DC, 2022)
Transitioning to a more knowledge- and technology-based economy will be critical if Bulgaria is to achieve convergence with its European peers in terms of economic productivity and living standards. The coming year presents an important opportunity for Bulgaria to improve its support for science, technology, and innovation (STI). This report assesses the efficiency of selected Bulgarian STI support programs, tracks progress on outcomes, and reports on beneficiaries’ perceptions of program quality. This report is the third and final major component of the World Bank’s Bulgaria public expenditure review for STI (PER STI) project. This efficiency analysis addresses an identified gap in Bulgaria’s STI system: the monitoring and evaluation (M and E) of STI support programs. This report aims to address those gaps by identifying benchmarks for assessing the results of STI support programs in Bulgaria and providing a methodology and tools for carrying out such evaluations in the future. The report is structured in nine sections. Section one presents the methodology, section two provides a comparison of key results across the six programs included in the analysis, sections three through eight provide program-specific analysis and findings, and section nine provides recommendations.